Key Role of Boron Compartmentalisation-Related Genes as the Initial Cell Response 1 to Low B in Citrus Genotypes Cultured In Vitro - Martínez-Cuenca, Mary-Rus; Primo-Capella, Amparo; Forner-Giner, María A. (Springer, 2020)
This work compared the expression of the main B transport-related genes (some members of the aquaporin family -NIP5, TIP5 and PIP1- and some efflux-B transporters -BOR1 and BOR4-), and the response of some physiological parameters in two citrus species [Citrus macrophylla W. (CM) and Citrus aurantium L. (CA)] under moderate and low boron (B) conditions. Seedlings were cultured “in vitro” in media supplemented with 50 or 0 μM H3BO3. NIP5, BOR1 and PIP1 expressions were enhanced by low B levels in both genotypes. TIP5 was down-regulated in the roots and leaves of the CA0 seedlings, and in the roots of CM0. BOR4 also lowered in the roots of both species at 0 μM H3BO3. Consequently, citrus species showed a common tolerance mechanism to low B conditions based on the synergism among transport channel NIP5, non-selective aquaporin PIP1 and transporter BOR1, and the impairment of genes TIP5 and BOR4 related with tolerance responses to B-toxic conditions. However, the CA genotype displayed low B symptoms earlier than CM (reduced plant biomass, length, relative growth rate and chlorophyll content). Proline concentration was higher in CM0 than in CA0 leaves, while the latter also enhanced malonaldehyde content. Although both plants had similar B concentrations, they differed in B content and B partitioning fractions. Whereas the CA genotype was more affected by lack of B treatment as more B was needed inside the cell, the more minimal need of cell B in CM favoured its allocation in the insoluble fraction and allowed growth in this genotype. In conclusion, B compartmentalisation seems critical in tolerance to low B level in citrus.